2015
DOI: 10.1093/conphys/cou061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthropogenic noise on endocrine and reproductive function in White's treefrog,Litoria caerulea

Abstract: Urbanization brings the introduction of roads and anthropogenic noise. Noise has negative health outcomes across vertebrates. White's treefrogs (Litoria caerulea) exposed to ecologically relevant levels of traffic noise for one week had elevated circulating corticosterone levels and decreased sperm count and sperm viability relative to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…The results reported in this study are consistent with the literature documenting the effects of anthropogenic noise on stress and hearing; however, this is the first study to investigate the effects of terrestrial traffic noise on an otophysan, freshwater stream fish [ 8 , 14 , 21 ]. The elevation in C .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results reported in this study are consistent with the literature documenting the effects of anthropogenic noise on stress and hearing; however, this is the first study to investigate the effects of terrestrial traffic noise on an otophysan, freshwater stream fish [ 8 , 14 , 21 ]. The elevation in C .…”
Section: Discussionsupporting
confidence: 90%
“…Currently, there is a growing volume of literature documenting the deleterious effects of anthropogenic noise on acoustic communication in the natural world [ 8 10 ]; although one study with birds found no effect of road noise on stress hormones [ 11 ]. Noise generated from human-related activities, such as transportation networks, commercial shipping, seismic exploration, resource extraction, and urbanization presents a unique challenge to organisms in both terrestrial and aquatic environments [ 12 14 ]. Anthropogenic noise often has frequencies similar to those utilized by vertebrates that communicate acoustically, effectively masking communication networks [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The energetic cost of calling in frogs is well recognized [ 57 ] and so the consequences of increased vocal output in response to noise, which could lead to a use of more energy reserves [ 27 ]. Therefore, although its yet to be more explored, changing call parameter can affect not only calling activity, but indirectly the animals life function and vital rates [ 5 , 34 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, few studies to date have been able to simultaneously measure environmental quality, GCs, and fitness consequences, leading to variable results that can be sex‐ (Strasser and Heath ), season‐ (Escribano‐Avila et al ), or scale‐ (i.e. individual versus population) specific (Riechert et al ), or only evident when other measures of physiology are accounted for (thyroid hormone: Hayward et al ) (but see Gobush et al , Sheriff et al , Kaiser et al ). Overall, we currently lack information regarding the spatial scale over which differences in such relationships can occur, whether they change over different stages in the life cycle, and how they can be further impacted by additional environmental change (e.g.…”
mentioning
confidence: 99%